Kajian Hak Tenurial Masyarakaat Adat Dalam Pengelolaan Hutan di Dusun Melinani Kecamatan Seram Utara Kabupaten Maluku Tengah - Mailissa, Ani; Silaya, Thomas M; Marasabessy, Husain; Sahureka, Mersiana (Universitas Pattimura, 2021)
The tenure rights of indigenous peoples over the management of natural resources is an exciting topic because the existence of indigenous law communities depends on forest natural resources. This study aims to find out the types of rights of indigenous peoples in forest management in Melinani Hamlet. The method used in this study is a qualitative descriptive method. The data collection techniques used are interviews and observation techniques. The results of the survey showed the tenure rights of the people of Melinani Hamlet, North Seram District of Central Maluku Regency, included six types of rights, namely extraction rights, management rights, renting rights, guaranteed rights, selling rights, and inheritance rights to access and manage forests in Hkm. The land tenure system is based on petuanan, clan, and individuals with diverse utilization patterns. According to soa Mailissa's predominantly land tenure, the land tenure system includes extraction rights, management rights, and inheritance rights. The marga system by the Mailissa Clan and individually carried out by the head of the family.